2019
DOI: 10.24251/hicss.2019.533
|View full text |Cite
|
Sign up to set email alerts
|

Nudging the Classroom: Designing a Socio-Technical Artifact to Reduce Academic Procrastination

Abstract: Procrastination is a widespread detrimental human behavior. Virtually everyone delays the initiation or completion of important tasks at times. Some people procrastinate to the point that they become overwhelmed by their inaction. In particular, academic procrastination is estimated to afflict 70 to 90% of undergraduate college students. We adopt the design science problem-solving paradigm to pilot a socio-technical artifact that reduces academic procrastination in large college classrooms. We adopt the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The companies which try to replace their workers entirely with AI will miss the full potential that AI brings (Wilson and Daugherty 2018a) or may even run into problems, as Tesla did. Thus, the big challenge of future research should not be about finding ways to deal with the replacement of humans by technology, but how intelligent and autonomous technology can be applied to human work tasks in order to improve human performance (Rodriguez et al 2019). Moreover, we should think of the ways to adjust the work tasks and to allow a close collaboration of individuals with the machine (McKendrick 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The companies which try to replace their workers entirely with AI will miss the full potential that AI brings (Wilson and Daugherty 2018a) or may even run into problems, as Tesla did. Thus, the big challenge of future research should not be about finding ways to deal with the replacement of humans by technology, but how intelligent and autonomous technology can be applied to human work tasks in order to improve human performance (Rodriguez et al 2019). Moreover, we should think of the ways to adjust the work tasks and to allow a close collaboration of individuals with the machine (McKendrick 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A facilitator is a nudge that assists individuals who are motivated, a spark is a nudge that motivates individuals who are able, and a signal is simply a reminder for individuals who are motivated and able. These three types of nudges were adopted in the study of Rodriguez et al (2019) in which automated interactive digital nudging software was employed during a large college course to reduce procrastination and increase performance. They found that students who chose to interact with the software performed better on the exam than students who did not (Rodriguez et al, 2019).…”
Section: Fogg Behaviour Modelmentioning
confidence: 99%
“…These three types of nudges were adopted in the study of Rodriguez et al (2019) in which automated interactive digital nudging software was employed during a large college course to reduce procrastination and increase performance. They found that students who chose to interact with the software performed better on the exam than students who did not (Rodriguez et al, 2019). Another application of the FBM in education, was to frame an investigation into changes in teacher's motivation and ability to use digital technologies, during the Covid-19 pandemic-enforced transition to online teaching (Beardsley et al, 2021).…”
Section: Fogg Behaviour Modelmentioning
confidence: 99%
“…In 10 articles the nudge changes its appearance or design due to individuals' behavior in the choice environment. For example, an individual performing a specific action (e.g., asking a question to a chatbot [54] or trying to write a social media post [55]) triggers the software to display a nudge adapted to that action. Thus, the bearer of the nudge interacts with the users and adapts the nudge to the individual's behavior in a simple way.…”
Section: Digital Component Of Nudgingmentioning
confidence: 99%